Estudio de megaesófago congénito en perro - Boix Vega, Carlota; Lafuente Carballo, Sofía; Martí Angulo, Simón; Sanchez de la Muela, Mercedes (Revista Complutense de Ciencias Veterinarias, 2009)
The megaesophagus is a condition that is the permanent dilatation of all or part of the esophagus. It is a rare and some of its causes are still under study. The patient in this case was a German Shepherd owned by the Guide Dog Foundation of Eleven, which had an esophageal dilatation until cardiac base, which was diagnosed fourth aortic arch persistent. In the surgical treatment was ruled out this diagnosis found that no vascular ring. The differential diagnosis of megaesophagus is complex and sometimes can lead to diagnostic errors that vary substantially the treatment and prognosis of the patient.